Strategi Event Branding Plupuh Batik Karnival Dalam Upaya Memperkenalkan Produk Batik Kabupaten Sragen Jawa Tengah 2024 - Dani, Jeratallah Aram; Setiawan, Ali Arif; Syaifullah, Jahid (AGUNA: Jurnal Ilmu Komunikasi, 2025)
Branding events are a means of company promotion in an effort to introduce new products to the public. Branding planning in supporting marketing communications is very closely related to advertising media, both through top-line media and bottom-line media. The plupuh batik carnival activity is an event planned in an effort to introduce Sukowati motif batik to the public. This research uses a qualitative method with a case study approach, to reveal the event branding strategy carried out by the committee in providing event and product information to the public.The result is an event strategy planned by the committee through collaboration with top-line media through radio and TV and bottom-line in the form of posters, banners, billboards and through online media to reach a wide and anonymous audience.